Do we need a different staging system for tongue and gingivobuccal complex squamous cell cancers?. (March 2018) - Gupta, Piyush; Migliacci, Jocelyn C.; Montero, Pablo H.; Zanoni, Daniella Karassawa; Shah, Jatin P.; Patel, Snehal G.; Ganly, Ian
Highlights: GBCSCC has a different clinicopathological profile than TSCC. GBCSCC tends to present in older patients with advanced stage compared to TSCC. Consistent decline in 5-year OS with worsening stages for either subgroups. Multivariate analysis – subsite is not an independent predictor of outcome. No justification to have a different staging system for GBCSCC. Abstract: Objectives: To determine the need for a separate staging system for gingivobuccal complex squamous cell cancers (GBCSCC) based on 5-year overall survival (OS), disease-specific survival (DSS), and recurrence-free survival (RFS) data from one institution. Patients and methods: An Institutional Review Board (IRB)-approved retrospective analysis was performed on an oral cavity cancer patient database. Patients from 1985 to 2012 with primary surgical treatment for biopsy-proven squamous cell cancer (SCC) from either the oral tongue (TSCC Group) or gingivobuccal complex (GBCSCC Group), were selected as two separate subgroups. The clinicopathologic data were used to stage the patients based on the American Joint Committee on Cancer 7th edition. Survival outcomes including 5-year OS, RFS, and DSS were calculated and analyzed. A multivariate analysis was performed to identify if subsite was an independent predictor for the survival outcomes, adjusting for other variables. A p-value of less than .05 was considered statistically significant. Results: 936 patients with TSCC and 486 patients with GBCSCC were considered eligible for the analysis. Patients with GBCSCC were more likely to be older (p < .001) and presented with more advanced disease (p < .001) compared to patients with TSCC. Unadjusted hazard ratio (HR) suggested GBCSCC had poor OS compared to TSCC. However, after adjusting for other variables, the adjusted HR was not significant (p = .593). There was no difference in 5-year DSS or RFS in either of the study groups. Conclusion: With similar survival outcomes by stage, there is no justification for using a different staging system for GBCSCC.